Why are Low-Income Teens More Likely to Lack Health Insurance Than Their Younger Peers? - Lindsey Jeanne Leininger; Marguerite E. Burns (SAGE Publishing, 2011)
Low-income teenagers are more likely to lack health insurance than younger children. Using data from the 2006, 2007, and 2008 rounds of the National Health Interview Survey, we examine whether differences between teens and younger children in socioeconomic factors, public health insurance eligibility, and observable family characteristics explain this apparent age-related coverage gap. Somewhat surprisingly, they do not. We find a highly robust age-coverage gradient among poor and near-poor children. Our results suggest the need to examine teen-specific insurance enrollment dynamics, particularly in families with no younger siblings, to optimize the effect of the newly enacted Patient Protection and Affordable Care Act on teens' insurance coverage.